2006
DOI: 10.2176/nmc.46.46
|View full text |Cite
|
Sign up to set email alerts
|

Safe Removal of Glioblastoma Near the Angular Gyrus by Awake Surgery Preserving Calculation Ability-Case Report-

Abstract: A 67-year-old patient presented with progressive agraphia, alexia, and impaired ability to calculate persisting for 4 weeks. He showed preserved ability to do single-digit addition and subtraction. Magnetic resonance imaging demonstrated a tumor in the left parietal lobe. A malignant glioma was suspected, and awake craniotomy was performed to remove the tumor with functional cortical mapping to determine the cortices involved in calculation and language. His calculation ability was mapped on the angular gyrus,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
8
0
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(9 citation statements)
references
References 30 publications
(40 reference statements)
0
8
0
1
Order By: Relevance
“…7,19,22,34 Few reports have characterized language morbidity following resection of intrinsic tumors from this brain region. 14,18,20,21,29,31 This study represents the largest reported experience with dominant IPL glioma resection, and it provides evidence that it is safe, but not risk-free, to resect these lesions.…”
Section: Discussionmentioning
confidence: 79%
See 1 more Smart Citation
“…7,19,22,34 Few reports have characterized language morbidity following resection of intrinsic tumors from this brain region. 14,18,20,21,29,31 This study represents the largest reported experience with dominant IPL glioma resection, and it provides evidence that it is safe, but not risk-free, to resect these lesions.…”
Section: Discussionmentioning
confidence: 79%
“…6,9,32 To date, however, only a few case series and case reports have investigated functional language outcomes following tumor resection from the IPL. 15,18,20,21,29 The purpose of this study was to define language outcomes in a series of consecutive patients who underwent glioma resection from the dominant IPL. In the majority of cases, these resections were performed with intraoperative mapping.…”
mentioning
confidence: 99%
“…conducted volumetric measurements of pre-and postoperative imaging. For low-grade gliomas, manual segmentation was performed with region-of-interest analysis to measure tumor volumes (cm 3 ) on the basis of FLAIR or T2 axial slices, as previously described. Extent of resection was calculated as (preoperative tumor volume − postoperative tumor volume)/preoperative tumor volume.…”
Section: Volumetric Analysesmentioning
confidence: 99%
“…On the other hand, calculation mapping with 5 Hz rTMS was able to induce a maximum error rate (ER) of 30% in the left AG for a single-digit multiplication task (Maurer et al, 2016 ). Similarly, direct cortical stimulation (DCS) close to the left AG in patients with tumors in the left parietal area disrupted the performance in single-digit addition, subtraction, and multiplication (Whalen et al, 1997 ; Duffau et al, 2002 ; Kurimoto et al, 2006 ). In a patient with a low-grade glioma in the right temporal cortex, DCS of the right AG also disrupted single-digit subtraction (Yu et al, 2011 ).…”
Section: Introductionmentioning
confidence: 99%